Peculiarities of Psychological Adaptation of Latin American Students to a New Social-Cultural Environment - O V Maslova (Peoples' Friendship University of Russia (RUDN University), 2012)
This article shows the basic results of the author's empirical studies, which target the different aspects of the psychological adaptation of Latin American students in Russia. The author describes and analyzes the major difficulties, styles, dynamics and gender differences of Latin American students' adaption to a new sociocultural environment. Some special features of the mutual interpersonal perception of Russians and Latin Americans are examined.